Analysis of gas pressure decline SF6 in 70kV circuit breaker bay transformer 3 at Babakan substation - Arif Ramdhan Achmad; Muhammad Soleh; Sugeng Suprijadi (PT Pustaka Intelektual Sutajaya, 2025)
This study analyzes the decrease in SF₆ gas pressure in the 70 kV circuit breaker Transformer Bay 3 at Babakan Substation, which affects the reliability of the power system. SF₆ gas is used as an insulating medium due to its high dielectric strength but is susceptible to micro-leakage, which degrades equipment performance. This research employs a qualitative approach with a case study strategy based on primary data obtained from field observations, interviews, and testing documentation before and after the replacement of the T-phase pole. Gas pressure monitoring was conducted using a FLIR Gas 306 camera and digital measuring instruments, with thematic analysis employed to identify causes and evaluate repair effectiveness. The results showed that a fine leak at the lower T-phase pole was the main cause of gas pressure reduction. After pole replacement, the rate of pressure drop decreased from 0.00459 MPa/day to 0.00016 MPa/day, indicating a 35.3% increase in insulation effectiveness and a 64.6% reduction in leakage rate. Operational feasibility tests met the SPLN 52-1:1983 standard, confirming that the circuit breaker is suitable for operation. I while applying condition-based maintenance (CBM) and infrared detection proved efficient in identifying SF₆ leakage and supporting predictive maintenance practices at substations.